Loma Negra: A Settlement of the Initial Period at the Casma coastline - Arrelucea Mafaldo, Leonardo (2018)
The valley of Casma has the greatest concentration of monumental settlements of the Initial Period in the Peruvian Coastline. In contrast, there is an archaeological void regarding the study of non-monumental settlements in this valley as well as lack of studies in the southern section of the Casma littoral.To fill this gap, in 2015 we conducted a survey and excavations in this area, with the goal of identifying domestic settlements contemporary with Las Aldas and of the same type to study their characteristics. In this paper, I show the preliminary results of the site “Loma Negra”. This research is based on the excavations at this site to infer the function, diet and types of activities developed on this site until now unknown for the archaeological community.